2012
DOI: 10.1309/ajcpp40mexwyrlpn
|View full text |Cite
|
Sign up to set email alerts
|

Flow Cytometric Findings in Hemophagocytic Lymphohistiocytosis

Abstract: Hemophagocytic lymphohistiocytosis (HLH) is an often fatal hyperinflammatory syndrome. HLH may be inherited, but it more commonly arises secondary to Epstein-Barr virus (EBV) or other infections, hematologic malignancies, or rheumatologic diseases. We identified 17 patients diagnosed with HLH who had flow cytometric analysis of peripheral blood or bone marrow performed at the time of diagnosis. Two patients had primary HLH, and the others had HLH secondary to EBV infection, hematologic malignancies, rheumatolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
33
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 17 publications
5
33
1
Order By: Relevance
“…compared T‐cell phenotype patterns among patients with proven genetic primary HLH and patients with secondary HLH. Consistent with prior reports and clinical practice in some centers , HLA‐DR expression was able to differentiate patients with HLH from controls. Notably, the authors observed that an optimal diagnostic cut‐off of HLA‐DR expression percentage of 14% among CD8 + T cells and 5% among CD4 + T cells offered sensitivities and specificities ranging from 83 to 98%.…”
supporting
confidence: 88%
“…compared T‐cell phenotype patterns among patients with proven genetic primary HLH and patients with secondary HLH. Consistent with prior reports and clinical practice in some centers , HLA‐DR expression was able to differentiate patients with HLH from controls. Notably, the authors observed that an optimal diagnostic cut‐off of HLA‐DR expression percentage of 14% among CD8 + T cells and 5% among CD4 + T cells offered sensitivities and specificities ranging from 83 to 98%.…”
supporting
confidence: 88%
“…Reports on the role of flow cytometry in diagnosing HLH on bone marrow aspirates show promise and may assist in increasing the pick-up rate. [1,24] It is hoped that this case series raises awareness of adult acquired HLH in intensivists, oncologists, physicians and infectious disease experts.…”
mentioning
confidence: 96%
“…[1][2][3][4] HLH is a group of disorders that include familial and acquired forms of the syndrome and macrophage activation syndrome that is associated with certain autoimmune diseases. [1][2][3]5 The acquired form of HLH is associated with infections, especially with Epstein-Barr virus, and malignancies, particularly peripheral T/NK-cell or anaplastic large cell lymphomas, and certain medications used for conditions such as systemic lupus erythematosus.…”
mentioning
confidence: 99%